Value of measurable residual disease monitoring in patients with acute promyelocytic leukemia in the era of frontline 'chemotherapy-free' therapy. Issue 3 (23rd February 2022) - Ramos Perez, Jorge M.; Patel, Keyur P.; Loghavi, Sanam; Garcia-Manero, Guillermo; Borthakur, Gautam; Jabbour, Elias; Wierda, William; Pierce, Sherry; Brandt, Mark; Kornblau, Steven; Kadia, Tapan; Daver, Naval; et al.
Abstract: Acute promyelocytic leukemia (APL) is characterized by the chromosomal translocation t (15;17) and the resulting gene PML-RARA, used for measurable residual disease (MRD) monitoring. Despite highly effective therapy for APL, MRD monitoring practices are not fully established. We aimed to assess the value of MRD monitoring by RT-qPCR in patients with APL treated with ATRA and arsenic trioxide +/– GO. We reviewed 223 patients with APL treated with this regimen. RT-qPCR for PML-RARA was measured every 3 months, and at 12, 18, and 24 months after therapy. Seven patients relapsed. Time to relapse was 7.9–12.4 months in 6 patients, and one patient relapsed after 79.5 months. These data show that MRD monitoring may be important for the detection of relapse in patients treated with this regimen within one year after completing therapy, however, since late molecular relapse is rare, our data suggest a low value of MRD monitoring beyond that first year.